Canine Periosteal Osteosarcoma - Gabriela, Noronha de Toledo; Pamela, Rodrigues Reina Moreira (Journal of Veterinary Healthcare, 2017)
Periosteal osteosarcoma is an uncommon primary malignant bone tumor in dogs and humans. This type of tumor is one of the four variants of osteosarcoma. The main feature is a superficial lesion without evidence of bone marrow involvement. The treatment usually performed is limb amputation. There is insufficient data on long-term disease-free time, surgical resection or local recurrence in dogs. The present review aims to gather information on periosteal osteosarcoma in dogs
Keywords: bone tumor; dogs; lameness; mesenchymal tumor; periosteum; periosteal osteosarcoma; veterinary oncology.